Culturally Relevant Pedagogy in Practice: Insights from Elementary School Classrooms - Niman, Erna Mena; Ntelok, Zepisius Rudiyanto Eso (Yayasan Keluarga Guru Mandiri, 2026)
The integration of local culture into elementary social studies instruction has become increasingly important in promoting culturally responsive and meaningful education. To create a more meaningful and contextually relevant learning environment, this qualitative case study aims to investigate how teachers integrate local cultural values into their instructional strategies. Ten elementary school teachers were purposefully selected to participate in the study, and data were collected through in-depth interviews, classroom observations, and a review of lesson plans and instructional materials. Patterns and themes in the data were found using thematic analysis. The results show that teachers utilize field studies, local folktales, and collaborative studies with community leaders to incorporate local culture creatively. However, challenges such as limited cultural relevance in textbooks and the lack of teaching resources hinder the effectiveness of integration. The study concludes that integrating local culture enhances students' cognitive and emotional engagement with the material, fostering a stronger cultural identity and character development. Recommendations for future research include expanding the study's scope to include more schools, examining the long-term effects on students' social and character development, and fostering greater collaboration between schools and local communities.